Physics and Histologic Evaluation of Rotary, Ultrasonic, and Sonic Instruments. Issue 7 (October 2017) - Ruga, Emanuele; Amerio, Ettore; Carbone, Vincenzo; Volante, Marco; Gandolfo, Sergio
Abstract : Abstract: Rotary instruments (RIs) are the most commonly used to perform osteotomies in many fields of medicine. Owing to a new interest in performing a minimally invasive surgery, over last fifteen years new devices have been used in oral surgery such as ultrasonic instruments (UIs) and, lately, sonic instruments (SIs). Nowadays, bone preservation and regeneration are paramount in many clinical situations and, consequently, it is crucial to rely upon instruments, which cause the least tissue damage during the surgery. Concerning SIs, there is still few information about workload to be applied and related temperature increases; furthermore, there are no comparative in-vivo studies, which analyze the thermal and mechanical effects on bone. Thus, SIs have been compared with UIs and RIs in terms of heat generation, operating time, accuracy, and tissue damage. Decalcification and sectioning procedure resulted in no significant differences between the applied instruments in terms of bone damage. RIs resulted more efficient than UIs ( P  < 0.001), but demonstrated low accuracy (NRS 4.9), whereas SIs ( P  = 0.005) required more time to perform the osteotomy. The maximum temperature increase occurred in the ultrasonic group. Even though SI were the slowest, they have proved to be the most accurate (NRS 8.4) in comparison with UI (NRS 7.6) and RI (NRS 4.9). Within the limit of this study, sonic instruments could be considered a safe alternative to ultrasonic instruments.